"Healthy immigrant effect" among individuals experiencing homelessness in Spain?: Foreign-born individuals had higher average age at death in 15-year retrospective cohort study - Fran Calvo; Ana Guillén; Xavier Carbonell; Rebeca Alfranca; Marta Beranuy; Alícia Parés-Bayerri; Sílvia Font-Mayolas (BMC, 2023)
Abstract Background Individuals experiencing homelessness (IEHs) suffer from severe health inequities. Place of origin is linked to health and mortality of IEHs. In the general population the "healthy immigrant effect" provides a health advantage to foreign-born people. This phenomenon has not been sufficiently studied among the IEH population. The objectives are to study morbidity, mortality, and age at death among IEHs in Spain, paying special attention to their origin (Spanish-born or foreign-born) and to examine correlates and predictors of age at death. Methods Retrospective cohort study (observational study) of a 15-year period (2006-2020). We included 391 IEHs who had been attended at one of the city's public mental health, substance use disorder, primary health, or specialized social services. Subsequently, we noted which subjects died during the study period and analyzed the variables related to their age at death. We compared the results based on origin (Spanish-born vs. foreign-born) and fitted a multiple linear regression model to the data to establish predictors of an earlier age at death. Results The mean age at death was 52.38 years. Spanish-born IEHs died on average almost nine years younger. The leading causes of death overall were suicide and drug-related disorders (cirrhosis, overdose, and chronic obstructive pulmonary disease [COPD]). The results of the linear regression showed that earlier death was linked to COPD (b = − 0.348), being Spanish-born (b = 0.324), substance use disorder [cocaine (b =-0.169), opiates (b =.-243), and alcohol (b =-0.199)], cardiovascular diseases (b = − 0.223), tuberculosis (b = − 0.163), high blood pressure (b =-0.203), criminal record (b =-0.167), and hepatitis C (b =-0.129). When we separated the causes of death for Spanish-born and foreign-born subjects, we found that the main predictors of death among Spanish-born IEHs were opiate use disorder (b =-0.675), COPD (b =-0.479), cocaine use disorder (b =-0.208), high blood pressure (b =-0.358), multiple drug use disorder (b =-0.365), cardiovascular disease (b =-0.306), dual pathology (b =-0.286), female gender (b =-0.181), personality disorder (b =-0.201), obesity (b =-0.123), tuberculosis (b =-0.120) and having a criminal record (b =-0.153). In contrast, the predictors of death among foreign-born IEHs were psychotic disorder (b =-0.134), tuberculosis (b =-0.132), and opiate (b =-0.119) or alcohol use disorder (b =-0.098). Conclusions IEHs die younger than the general population, often due to suicide and drug use. The healthy immigrant effect seems to hold in IEHs as well as in the general population.